Cracking the code to female sexual satisfaction: the serial mediation of sexual behavior and the perceived importance of healthy sexuality from sexual self-efficacy - Ogallar-Blanco, Adelaida Irene; Lara-Moreno, Raquel; García-Pérez, Raquel; Liñán-González, Antonio; Godoy-Izquierdo, Débora (Frontiers in Psychology, 2024)
Introduction Sexual satisfaction has been shown to have a strong association with many aspects of sexual health and wellbeing. It is further considered a robust indicator of an individual’s health status and general wellbeing, revealing that a person can enjoy pleasurable and healthy sexual experiences, beyond the mere absence of sexual and reproductive health issues. Objectives This study aimed to analyze the relationship between sexual satisfaction, sexual behaviors, sexual self-efficacy, and the importance personally attributed to maintaining an active and satisfying sexual life among young and middle-aged women aged 18–50. Design A descriptive correlational study with a cross-sectional design was conducted. Methods Participants (N = 1,076 women) completed self-reports on sexual self-efficacy beliefs, frequency of sexual behaviors, the importance attributed to active and healthy sexuality, and multidimensional sexual satisfaction. Results The supported mediation model indicated that sexual self-efficacy was related to sexual satisfaction directly and indirectly through sexual behavior and a serial path through sexual behavior and the perceived importance of healthy sexuality. The total effect was significant, and the full model explained 7.3% of the global sexual satisfaction variance (F = 17.218, p = 0.000), with the mediated effect accounting for 44.3%. Conclusion This study confirms a partial serial mediation model by which sexual self-efficacy significantly predicts sexual satisfaction through sexual behaviors and the importance attributed to a healthy sexuality. Due to its significant contribution, the perceived importance of sexuality should be considered when studying correlates of sexual satisfaction. These findings have interesting implications for the development of strategies aimed at sexual health promotion and sexual education among women in early and middle adulthood.